Distinct properties underlie flavin-based electron bifurcation in a novel electron transfer flavoprotein FixAB from Rhodopseudomonas palustris - Duan, H. Diessel (J Biol Chem, 2018)
A newly recognized third fundamental mechanism of energy conservation in biology, electron bifurcation, uses free energy from exergonic redox reactions to drive endergonic redox reactions. Flavin-based electron bifurcation furnishes low-potential electrons to demanding chemical reactions, such as reduction of dinitrogen to ammonia. We employed the heterodimeric flavoenzyme FixAB from the diazotrophic bacterium Rhodopseudomonas palustris to elucidate unique properties that underpin flavin-based electron bifurcation. FixAB is distinguished from canonical electron transfer flavoproteins (ETFs) by a second FAD that replaces the AMP of canonical ETF. We exploited near-UV–visible CD spectroscopy to resolve signals from the different flavin sites in FixAB and to interrogate the putative bifurcating FAD. CD aided in assigning the measured reduction midpoint potentials (E° values) to individual flavins, and the E° values tested the accepted model regarding the redox properties required for bifurcation. We found that the higher-E° flavin displays sequential one-electron (1-e(−)) reductions to anionic semiquinone and then to hydroquinone, consistent with the reactivity seen in canonical ETFs. In contrast, the lower-E° flavin displayed a single two-electron (2-e(−)) reduction without detectable accumulation of semiquinone, consistent with unstable semiquinone states, as required for bifurcation. This is the first demonstration that a FixAB protein possesses the thermodynamic prerequisites for bifurcating activity, and the separation of distinct optical signatures for the two flavins lays a foundation for mechanistic studies to learn how electron flow can be directed in a protein environment. We propose that a novel optical signal observed at long wavelength may reflect electron delocalization between the two flavins.